2013
DOI: 10.1152/ajprenal.00172.2012
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal hyperoxia: effects on nephrogenesis and long-term glomerular structure

Abstract: Preterm neonates are born while nephrogenesis is ongoing and are commonly exposed to factors in the extrauterine environment that may impair renal development. Supplemental oxygen therapy exposes the preterm infant to a hyperoxic environment that may induce oxidative stress. Our aim was to determine the immediate and long-term effects of exposure to hyperoxia, during the period of postnatal nephrogenesis, on renal development. Newborn mice (C57BL/6J) were kept in a normoxic (room air, 21% oxygen) or a controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 35 publications
(56 reference statements)
2
32
0
Order By: Relevance
“…In this regard, we have previously shown that 80% O 2 exposure in the neonatal period results in vascular rarefaction, hypertension, and reduced nephron number in the adult rat [13], similar to clinical outcomes seen in children and adults that were born preterm [3][5]. In contrast, a recent study in a mouse model (mice exposed to 65% O 2 from birth to postnatal day 7) showed no changes in nephron number [33]; the differences in findings between studies may relate to differences in the concentration of oxygen used, the postnatal days of exposure, and also susceptibilities of the animal model.…”
Section: Discussionmentioning
confidence: 58%
“…In this regard, we have previously shown that 80% O 2 exposure in the neonatal period results in vascular rarefaction, hypertension, and reduced nephron number in the adult rat [13], similar to clinical outcomes seen in children and adults that were born preterm [3][5]. In contrast, a recent study in a mouse model (mice exposed to 65% O 2 from birth to postnatal day 7) showed no changes in nephron number [33]; the differences in findings between studies may relate to differences in the concentration of oxygen used, the postnatal days of exposure, and also susceptibilities of the animal model.…”
Section: Discussionmentioning
confidence: 58%
“…Studies conducted previously in a rat model of neonatal hyperoxia exposure (80% O 2 P3-P10, a time of ongoing postnatal nephrogenesis), found reduced glomerular size in neonates and a 25% reduction in nephron number in adulthood, suggesting that the kidney is adversely affected [14, 39]. Conversely, neonatal hyperoxia exposure (65% O 2 ) did not have any adverse renal effects in a mouse model [40]. Unlike these rodent models, in this more clinically relevant large animal model, nephrogenesis in the lamb was already completed, mechanical ventilation was used (and for a shorter time period of 3 days), and all animals were initially exposed to 100% O 2 then weaned to lower concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, this can lead to a number of common morbidities of prematurity such as, retinopathy of prematurity, necrotizing enterocolitis and bronchopulmonary dysplasia [169]. In the kidney of the human neonate, oxidative stress has been reported to cause tubular injury [170] and it has been linked to impairment of nephrogenesis in animal studies [171]. In the rat model (where nephrogenesis is ongoing in the first two weeks after birth), a significant reduction of nephrons (25%) was reported in adulthood (25-35 weeks of age) [171] following exposure to 80% oxygen during the early postnatal period.…”
Section: Hyperoxia and Ventilationmentioning
confidence: 99%